Estudio crítico : Martin Kusch A Sceptical Guide to Meaning and Rules. Defending Kripke's Wittgenstein, Montreal and Kingston, Ithaca, McGuill-Queen's University Press, 2006 - Karczmarczyk, Pedro (2007)
Fil: Karczmarczyk, Pedro. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.